Perbandingan Pajak di Negara Maju dan di Negara Berkembang - Burhanudin Yusuf; Haliza Nur Fazriyah; Indah Agnesia Wildani; Regita Dwi Azzahra (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2025)
This study discusses the comparison of taxation systems between developed and developing countries, focusing on the strategic role of taxes in national development, tax administration challenges, and the relationship between public service quality and taxpayer compliance. Using a descriptive qualitative approach with a case study method, this research compares Sweden, a developed country known for its transparent and efficient tax system, with Indonesia, a developing country that still faces challenges in tax collection and administration. The findings reveal that the success of a tax system depends greatly on transparency, public service quality, and public trust. In developed countries, taxes serve not only as state revenue but also as tools for income redistribution and economic control. Meanwhile, in developing countries, the main obstacles include low compliance, legal uncertainty, weak enforcement, and underdeveloped administrative culture. Therefore, tax reform is essential to improve tax system effectiveness and public participation. This study recommends regulatory improvement, increased tax literacy, and service innovation to build a fair, transparent, and sustainable tax system.